The influence of corporate social responsibility on firm performance with leverage as moderating variable in companies listed in SRI-KEHATI Index - Rosiana Rosiana; Akhmadi Akhmadi (Junal Ilmu Manajemen, 2023)
Companies listed on the SRI-Kehati index are companies that implement CSR in accordance with the principles of Sustainable and Responsible Investment. This study aims to analyze the effect of CSR on firm performance in companies listed on the SRI-Kehati Index in 2015-2020 with a sample of 20 companies. This study use leverage as moderating variabel to measure whether leverage can strengthen or weaken the effect of CSR on firm performance and use firm size as control variabel. The sampling method is purposive sampling method and based on the criteria obtained a sample of 20 companies. The results showed that CSR had a significant negative effect on firm performance, leverage had a significant negative effect on firm performance, company size had no significant effect on firm performance, and leverage was able to strengthen the effect of CSR on firm performance.